Evaluation of petrophysical properties using well logs of Khasib formation in east Baghdad oil field, central area - Hameed, Noor F.; AbdulMajeed, Rwaida K. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The assessment of petroleum characteristics through well log analysis has always been essential for identifying and evaluating hydrocarbon-bearing zones. This study presents a comprehensive re-evaluation and correction of five well log data sets from Khasib formation which is the primary reservoir in the East Baghdad oil field (10 kilometers east of Baghdad City). The corrected data sets were utilized to calculate key parameters, including water saturation, porosity, lithology, and shale volume. Lithology was determined using M-N cross-plots and neutron-density analysis, which showed that the Khasib formation mainly consists of limestone, with calcite as main mineral components and minor amounts of dolomite. Shale volume was assessed using both single and dual shale indicators. The three main logs of porosity neutron, density, and sonic logs were used for computing the porosity. Then, Archie equation was employed to determine water saturation. To verify the accuracy of the computation, a comparison between the results and the available core data was conducted, which indicated that porosity values ranged from 0.143 to 0.212, while water saturation varied from 0.643 to 0.951. In addition, core samples and geological reports confirmed that Khasib formation was clean with minimal shale content.